Pengaruh Motivasi Kerja dan Displin Kerja terhadap Kinerja Karyawan di Perusahaan PTPN X Pabrik Gula Lestari Kertosono - Nurindah Dwi Antika Sukiyah; Mujita Fajar Elok Venanda; Elok Venanda; Jojok Dwiridotjahjono (Jurnal Manajemen dan Organisasi, 2021)
The background in this study is how important it is for a leader to apply motivation and work discipline to the company to improve the performance of its employees, because with motivation and work discipline, employees will feel responsible for all their duties. This study aims to determine the effect of work motivation and work discipline on employee performance partially, and to determine the effect of work motivation and work discipline on employee performance simultaneously. The data analysis technique used in this study is multiple linear regression analysis, using the F test and t test. The results of multiple linear regression show that the work motivation variable has a significant effect on employee performance. Work discipline variables have a significant effect on employee performance. And Hail F test shows that there is a significant influence between the variables of Work Motivation and Work Discipline simultaneously affect the Employee Performance of PTPN X Lestari Sugar Factory (Kertosono). The conclusion from the results of this study is that increasing employee performance cannot be separated from work motivation (needs, attitudes, abilities, payment or salary, job security, fellow workers) and work discipline (always present on time, always prioritizing attendance percentage, always obeying the hourly provisions). work, always use working hours effectively and efficiently). With high work motivation and work discipline, it will be easier to improve employee performance.